Exploring the support needs of youth with mental health issues who are seeking employment in Northern Ontario - Aguiar, Katrina (My University, 2018)
Young people in northern communities experience several vulnerabilities related to employment and mental health. Although these vulnerabilities have been studied separately, very little research has been published on how they intersect. The present study focuses on youth aged 16-29 years who have experienced a self-identified mental health issue and are seeking employment in Northern Ontario. The purpose is to explore the interaction of employment and mental health challenges for youth living in northern communities, with a particular focus on youth support needs and youth service delivery preferences. Fifteen participants (eight youth and seven employment counsellors) were purposively sampled from a provincial youth employment program. Participants completed audio-recorded, semi-structured interviews about employment histories, mental health experiences and locally available services and supports. Transcripts were coded and analyzed using interpretive description methodology. Three themes emerged from the analysis, conceptualized using the metaphor of an employment journey. The first theme, “roadblocks”, captures the challenging life circumstances experienced by youth, including complexities related to geography, and describes how both can interfere with a young person’s employment success. The second theme, “pit stops”, describes the different ways youth come into contact with employment counsellors, and the critical role these individuals play in supporting young people in and out of the workplace. The final theme, “maps for success”, outlines what would be helpful for youth and for the employment counsellors that support them. Two key messages were elucidated from the results. First, the support needs of youth are complex, multi-layered and interdependent. Second, youth employment services are inadequately resourced to support young job seekers with complex needs. Findings are limited in their transferability to other service delivery contexts. Recommendations on how to respond to the complex, intersecting vulnerabilities of youth in Northern Ontario are provided.
YOUTH EMPLOYMENT & MENTAL HEALTH IN NORTHERN ONTARIO
Keywords: Employment; Mental Health; Northern Ontario; Youth; Qualitative Research; Interpretive Description